2013
DOI: 10.1080/10874208.2013.813180
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of EEG Alpha Rhythm of Artists and Nonartists During Visual Perception, Mental Imagery, and Rest

Abstract: In this article, differences in alpha power between multichannel EEG signals of artists and nonartists were investigated. The two groups were compared during visual perception, mental imagery, and at-rest conditions. We found no significant differences between the two groups in absolute alpha power at rest. Both absolute and relative alpha power were found to be significantly lower in artists during the visual perception and the mental imagery tasks for some of the channels, suggesting that the cerebral effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In addition, artists can mentally visualize a painting more capably due to their improved visual perception. This is because they know art and its significant characteristics [ 5 ]. Therefore, artists process more information during visual perception and mental imagery than nonartists, and increasing ApEn is reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, artists can mentally visualize a painting more capably due to their improved visual perception. This is because they know art and its significant characteristics [ 5 ]. Therefore, artists process more information during visual perception and mental imagery than nonartists, and increasing ApEn is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, a novice had to carry out the four visual perception tasks and significant changes in ApEn were measured. The progress of the participant is quantified by comparing the measured significant variation pattern to those obtained by expert artists while carrying out the similar tasks [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies found that the patterns of cortical activity of experts and nonexperts are different (Abernethy & Russell, 1987;Bhattacharyaa & Petsche, 2002;Bird, 1987;Collins, Powell, & Davies, 1990;Crews & Landers, 1993;Fink, Graif, & Neubauer, 2009;Hatfield, Landers, & Ray, 1984;Haufler, Spalding, Maria, & Hatfield, 2000;Karkare, Saha, & Bhattacharya, 2009;Panga, Nadalb, Müllerc, Rosenbergd, & Kleine, 2012;Petsche, Lindner, Rappelsberger, & Gruber, 1988;Petsche, Richter, Stein, Etlinger, & Filz, 1993;Radlo, Steinberg, Singer, Barba, & Melinkov, 2002;Salazar et al, 1990;Shourie, Firoozabadi, & Badie, 2011, 2013Wagner, 1975aWagner, , 1975b. Most of the previous research has focused on the power spectrum density of the traditional EEG rhythms, which may not be reliable due to the nonstationary nature of the EEG signals (Collins et al, 1990;Crews & Landers, 1993;Fink et al, 2009;Hatfield et al, 1984;Haufler et al, 2000;Petsche et al, 1988;Petsche et al, 1993;Radlo et al, 2002;Salazar et al,1990;Shourie et al, 2013;Wagner, 1975aWagner, , 1975b. Hence, time-frequency features are highly reliable for EEG signal analysis.…”
Section: Introductionmentioning
confidence: 99%